P22 Cardiac energy metabolism increases with ketone oxidation. (21st March 2018) - Chong, Cher-Rin; Cole, Mark; Carr, Carolyn; Lee, Henry; Stubbs, Brianna; Abdul Kadir, Azrul bin; Evans, Rhys; Cox, Pete; Clarke, Kieran
Abstract : Rationale: The oxidation of ketone bodies plus glucose improves the efficiency of the working rat heart by ~30% compared to glucose alone. 1 However, perfusions of hearts with ketones alone led to gradual functional decline with reduced flux through α-ketoglutarate dehydrogenase. 2 We have shown that that the rate of d-β-hydroxybutyrate (βHB) oxidation in isolated perfused rat heart increases with the glycogen content via replenishing anaplerotic substrates. Therefore, we aimed to determine whether the availability of glycogen increases the oxidation of ketones and improves myocardial energetics. Methods: Hearts from male Wistar rats (320–360 g) were isolated and perfused with buffer to alter the glycogen content, before perfusion with either 11 mM glucose or 11 mM glucose plus 4 mM βHB. Fully relaxed 31P-MR spectra were acquired at each stage of the protocol to measure pH, PCr, Pi and ATP concentrations ([PCr], [Pi], [ATP]). Results were analysed using 2-way ANOVA with Bonferroni's correction. Results: [ATP] remained constant under all perfusion conditions, irrespective of the cardiac glycogen content. In hearts with high glycogen, addition of βHB increased [PCr] by 41%, from 15.4±0.5 to 21.7±0.5 mM, and ▵GATP by −6.3 kJ/mol (both p<0.001). In low glycogen hearts, addition of βHB did not alter [PCr] or ▵GATP. Conclusion: High glycogen concentrations increased the oxidation of βHB, thereby improving cardiac energetics. References: . Sato, et al. FASEB 1995;9(8):651–8. . Russell RR, Taegtmeyer H. JCI1991;87(2):384–390.